Computed tomography of the brain, chest, and abdomen in the preoperative assessment of non-small cell lung cancer. Issue 11 (November 1988) - Grant, D; Edwards, D; Goldstraw, P
Abstract : The benefit to be gained from carrying out computed tomography of brain and abdomen in addition to the chest has been evaluated retrospectively in 114 consecutive patients with non-small cell lung cancer who, on the basis of history, clinical examination, chest radiography, and bronchoscopy had been considered potentially operable. Computed tomography of the chest showed potentially inoperable tumour in 37 patients, of whom 25 had tumour confined to the chest. Three patients were shown to have malignant disease within the mediastinum and abdomen; five within the mediastinum and brain; and four within the mediastinum, abdomen, and brain. Computed tomography of the abdomen disclosed deposits in nine patients, but in only two were the abnormalities restricted to the abdomen. Computed tomography of the brain showed metastases in 10 patients, of whom only one had metastatic disease confined to the brain. Thus three patients had isolated deposits in the abdomen and brain. In 12 patients the identification of metastases in the abdomen and brain removed the need for mediastinoscopy. Preoperative computed tomography of the abdomen and brain detected occult metastases in 15 patients (13%) in this study. In three patients the extrathoracic abnormality proved the only contraindication to surgery, but in the other 12 it provided valuable corroborative evidence of incurability and facilitated the assessment of the mediastinal abnormality.